2010
DOI: 10.1021/jp100197c
|View full text |Cite
|
Sign up to set email alerts
|

BaFeO3−x Perovskite: An Efficient NOx Absorber with a High Sulfur Tolerance

Abstract: The noble metal free perovskite-type BaFeO3−x catalyst has been synthesized by a sol−gel method containing a small amount of spinel and carbonate. NO x is stored on both perovskite and carbonate, and the formed nitrate on the perovskite can be transferred to the neighboring carbonates to regenerate the storage sites on the perovskite. During the sulfation process, both perovskite and carbonate can be sulfated, and the sulfate species formed on the former one is more easily reduced. The poison of the perovski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 44 publications
2
33
0
4
Order By: Relevance
“…In the complex H 2 consumption profiles shown in Figure 6, three regions can be established [56,57,58]:At low temperature, between approximately 200 °C and 550 °C, a broad H 2 consumption signal is observed for all the catalyst that, according to literature, can be ascribed to different reduction processes: (i) the Cu(II) [34,38] reduction, (ii) the Fe(IV) and Fe(III) reduction to Fe(III) and Fe(II), as was observed for Fe 3 O 4 , and iii) the reduction of weakly chemisorbed oxygen upon surface oxygen vacancies of perovskite (α-oxygen) [34]. From around 550 °C to 700 °C, the H 2 consumption peaks correspond to both the reduction of Fe(III) to Fe(II) as detected for the reduction of Fe 3 O 4 to FeO and to the decomposition of surface oxygen species formed on oxygen vacancies (called α’-oxygen) [34], more strongly bonded to the perovskite than α-oxygen.At high temperatures (T > 700 °C), broad TCD signals assigned to the reduction of Fe(II) to Fe(0) (causing the consequent destruction of the perovskite structure) could be found [56,57,58]. Nevertheless, the XRD data for catalysts after H 2 -TPR (not shown) reveal that the perovskite structure is still present, thus, the reduction to Fe(0) is not taking place and, consequently, H 2 consumption is hardly observed at T > 700 °C.…”
Section: Resultsmentioning
confidence: 99%
“…In the complex H 2 consumption profiles shown in Figure 6, three regions can be established [56,57,58]:At low temperature, between approximately 200 °C and 550 °C, a broad H 2 consumption signal is observed for all the catalyst that, according to literature, can be ascribed to different reduction processes: (i) the Cu(II) [34,38] reduction, (ii) the Fe(IV) and Fe(III) reduction to Fe(III) and Fe(II), as was observed for Fe 3 O 4 , and iii) the reduction of weakly chemisorbed oxygen upon surface oxygen vacancies of perovskite (α-oxygen) [34]. From around 550 °C to 700 °C, the H 2 consumption peaks correspond to both the reduction of Fe(III) to Fe(II) as detected for the reduction of Fe 3 O 4 to FeO and to the decomposition of surface oxygen species formed on oxygen vacancies (called α’-oxygen) [34], more strongly bonded to the perovskite than α-oxygen.At high temperatures (T > 700 °C), broad TCD signals assigned to the reduction of Fe(II) to Fe(0) (causing the consequent destruction of the perovskite structure) could be found [56,57,58]. Nevertheless, the XRD data for catalysts after H 2 -TPR (not shown) reveal that the perovskite structure is still present, thus, the reduction to Fe(0) is not taking place and, consequently, H 2 consumption is hardly observed at T > 700 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the BaSnO 3 formulation exhibited limited sulfur resistance. In this sense, a BaFeO 3 catalyst developed latter by Xian et al [87,103,104] showed a lower decrease of NSC after sulfating (about 11-12%). The incorporation of Ti improves sulfur resistance in a higher extent; activity decreased only 5.1% after SO 2 -pretreatment of a BaFe 1− xTi x O 3 catalyst (x = 0.1 or 0.2).…”
Section: No-to-no 2 Conversion (X No-to-no2 First Column) No X Stomentioning
confidence: 88%
“…Hence, diffusion of intermediate compounds from oxidation to adsorption sites was facilitated. Among all prepared catalysts, 30% La 0.7 Sr 0.3 CoO 3 /Al 2 O 3 sample achieved the most efficient use of perovskite phase due to the best balance between well-developed perovskite phase and NO oxidation and NO adsorption site distribution such as oxygen vacancies, structural La and Sr at the surface, and segregated SrCO 3 [86,87].…”
Section: Evolution Of α Desorbed Oxygen Species and No-to-no 2 Convermentioning
confidence: 99%
“…Thus, the BaSnO3 perovskite had the largest NOx storage capacity. In a series of consecutive studies BaCoO3 [80,81] and BaFeO3 [82][83][84] perovskites were also explored as alternatives with high NOx storage capacity and notable sulfur resistance. In these materials, the presence of BaCO3 as an impurity promoted the NOx adsorption capacity; however, this phase limited the regeneration capacity after SO2 poisoning.…”
Section: No X Adsorption Under Oxidizing Conditionsmentioning
confidence: 99%